Technology acceptance in business analytics: A case study of a manufacturing company - Airikkala, Miikka (My University, 2026)
In today’s business, with every action in a production line or in the sales pipeline leaving its mark in the form of data, it goes through various steps and systems to possibly end up on a report. Managing a large amount of data efficiently is key in order to turn the bits and pieces of data into useful reports. To be able to create useful insights out of raw data is not only about the suitable technical approach but concerns many questions regarding the implementation and assimilation of the tools from the user’s perspective. The factors playing into the acceptance portray a big role in the successful utilisation of business analytics. The two main research questions that this study aims to answer are as follows: 1. What are the main drivers for technology acceptance from the business users’ perspective in business analytics? 2. How to accommodate the user needs in a large organization to the greatest extent possible? Data management and business analytics have been researched extensively, especially from the technical perspective through the whole process from ETL (extract-transform-load) to BI (business intelligence) reporting. Additionally, the Technology Acceptance Model (TAM) from Davis (1989) which explores the factors that affect the acceptance of technology from the user’s perspective has been researched in various contexts. This thesis aims to observe the factors that play a role in the acceptance and assimilation of business analytics tools in the framework of TAM. This thesis has been conducted as a case study about a Finnish company in the manufacturing industry. Some key business users who work with reporting-related topics were identified and contacted. The interviews were conducted as semi-structured interviews. The interview questions focused on the subjective experiences of the interviewees regarding the various tools and systems that they have experience with in general and in the field of reporting and analytics. The answers from the interviews showed that when it comes to business analytics, users seem to prioritize perceived usefulness over perceived ease of use. Most of the friction in the acceptance and assimilation stems from issues in communication or from bureaucratical challenges. Multiple interviewees identified themselves as early adopters with technology and expressed interest in taking up new reporting-related tools if possible. Regarding business analytics, the biggest hurdles in assimilation were the lack of knowledge around the possibilities and the bureaucratic processes. For the organization to be fully able to utilize the expertise of the users, focusing on communication and streamlining the processes around technology adoption seem to be the most recommendable actions. With the users seemingly equipped with a high level of ownership and keen on improving the results of their own work with up-to-date tools and systems even if it meant going through a steep learning curve, just having the tools and data readily available and well communicated appears to be the key to solving the majority of the issues the users are experience.

Liiketoiminnassa jokainen toiminta tuotantolinjalta myyntiputkeen jättää jäljen dataan, kulkien useiden vaiheiden ja järjestelmien läpi, päätyen usein raportille. Suuren datamäärän hallinnointi tehokkaasti on olennaista, jotta data saadaan muutettua hyödyllisiksi raporteiksi. Raakadatan muuttamisessa hyödylliseksi tietämykseksi ei ole kyse vain oikean teknisen ratkaisun valitsemisesta, vaan siihen liittyy myös monia näkökulmia käyttäjän perspektiivistä työkalujen käyttöönottoon ja omaksumiseen liittyen. Teknologiahyväksyntään vaikuttavilla tekijöillä on huomattava rooli liiketoiminta-analytiikan hyödyntämisessä. Tämän tutkimuksen kaksi päätutkimuskysymystä ovat: 1. Mitkä ovat teknologian hyväksyntään vaikuttavat pääajurit käyttäjän näkökulmasta liiketoiminta-analytiikassa? 2. Miten käyttäjien tarpeet liiketoiminta-analytiikan suhteen voidaan huomioida parhaan mukaan isossa organisaatiossa? Tiedonhallintaa ja liiketoiminta-analytiikkaa on tutkittu laajasti, erityisesti teknisemmästä prosessinäkökulmasta lähtien ETL-prosessista (extract-transform-load) BI-raportointiin (business intelligence) asti. Lisäksi teknologiahyväksyntään käyttäjän näkökulmasta vaikuttavia tekijöitä kuvaavaa Davisin (1989) TAM-mallia (Technology Acceptance Model) on tutkittu useissa eri konteksteissa. Tämän tutkimuksen tarkoituksena on perehtyä niihin tekijöihin, jotka vaikuttavat liiketoiminta-analytiikan työkalujen hyväksymiseen ja omaksumiseen TAM-mallin viitekehyksessä. Tämä tutkielma on toteutettuna case-tutkimuksena suomalaisesta valmistavan teollisuuden organisaatiosta. Tutkimusta varten pyrittiin tunnistamaan ja kontaktoimaan raportoinnin parissa työskenteleviä liiketoimintakäyttäjiä. Haastattelut toteutettiin puolistrukturoituina haastatteluina. Haastattelukysymykset keskittyivät haastateltavien subjektiivisiin kokemuksiin yleisesti erilaisten työkalujen ja järjestelmien kanssa sekä erityisesti raportointiin ja analytiikkaan liittyen. Haastateltavien vastauksista kävi ilmi, että liiketoiminta-analytiikasta puhuttaessa käyttäjät vaikuttavat suosivan koettua hyödyllisyyttä koetun helppokäyttöisyyden sijaan. Merkittävin kitka hyväksynnän ja omaksumisen suhteen vaikuttaa johtuvan ongelmista kommunikaatiossa tai byrokraattisista haasteista. Useat haastateltavat kertoivat identifioituvansa varhaisiksi omaksujiksi puhuttaessa teknologiasta osoittaen mielenkiintoa uusien raportointityökalujen käyttöönottoon mahdollisuuksien mukaan. Liiketoiminta-analytiikasta puhuttaessa suurimpia esteitä omaksumiselle olivat tietämättömyys mahdollisuuksista sekä byrokratia. Jotta organisaatio pystyisi parhaiten hyödyntämään käyttäjiensä asiantuntijuutta, suositeltavinta vaikuttaa olevan keskittyä kommunikaation kehittämiseen ja prosessien virtaviivaistamiseen käyttöönottoon liittyen. Käyttäjät osoittivat omistajuutta ja kertoivat mielenkiinnostaan parantaa oman työnsä tuloksia uusien työkalujen avulla huolimatta vaativastakin oppimisvaiheesta. Työkalujen ja datan saattaminen helposti saataville ja sen kommunikointi selkeästi vaikuttaa ratkaisevan suurimman osan käyttäjien kokemista ongelmista.
Keywords: business analytics, technology acceptance, reporting, IT, data management, liiketoiminta-analytiikka, teknologian hyväksyntä, IT, tiedonhallinta, raportointi